The role and impact of high throughput biomimetic measurements in drug discovery - Shenaz Bunnally; Rob J Young (International Association of Physical Chemists (IAPC), 2018)
During the early phase of drug discovery, it is becoming increasingly important to acquire the full physicochemical profile of molecules. For this purpose, there is a strong interest in developing efficient and cost-effective platforms for fast and reliable measurements of physicochemical properties. We have developed an automated physchem platform which ensures that consistent, comprehensive, and high-quality physicochemical property measurements and derived property information for 100's of compounds per week are available alongside potency data at the right time to guide compound progression decisions. We discuss the routine assessments of biomimetic properties using high throughput automated high-performance liquid chromatography (HPLC) platforms, with details of the methods and hardware employed, also with illustrations of the quality and impact of the data generated.